(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Businesses are implementing work-from-home policies because of social conventions that discourage collaboration and widespread lockdowns. Digitalization has forced an inescapable rise in the usage of digital technologies as it quickens national lockdowns and social distancing practices. Globally, individuals and institutions have embraced new modes of living and working. The whole payment system has been significantly impacted by the pandemic. Payments and money transfers made by consumers have been considerably influenced by COVID-19. Online commerce and the transition to cashless payment methods are only two examples of trends that have accelerated due to concerns about contagion. To take advantage of this acceleration, several fintech companies have increased features and extensively invested in client acquisition as individuals become more aware of such contactless options. Contactless transactions became important to both small and large businesses as cash payments became unsafe.